Notes from isolation: global criminological perspectives on coronavirus pandemic - Siegel, Dina (Eleven International Publishing, 2021)
This volume includes topics analysing the meaning of the Covid-19 pandemic and the social responses to it in various domains: from sex work to wildlife crimes, from new forms of social control in Brazil, Ecuador, Canada and Thailand to the role of music, symbolic of face masks, spread of conspiracy theories, domestic violence, and more. It is composed of studies conducted by criminologists who belong to ‘Utrecht school’. Criminology ‘Utrecht style’ is unique in the world in the sense that cultural, critical and global criminology are central to its research and teaching programme, ethnographic and netnographic methods are rigorously applied and further developed.The researches here presented – in all their variety, improvisation, and cross-pollination – contribute to the body of cultural criminological work, and go beyond. They explore themes and concepts underexposed in cultural criminology so far, and contribute to the further growth of this academic perspective through their combined understandings of crime and social reactions under extreme social circumstances